Experimental investigation on the quasi-static crush performance of resin-infused thermoplastic 3D fibre-reinforced composites - Shah, S.Z.H. (Elsevier Ltd, 2021)
This paper presents the quasi-static crush performance of newer resin-infused thermoplastic 3D fibre reinforced composites (FRC) under axial load. The main objective is to make an assessment of the energy absorption capability of novel 3D composites for improved energy absorbing applications. Flat specimens of resin-infused thermoplastic (TP) and thermoset (TS) 3D composites with three trigger angles, i.e., 15°, 30° and 45° were tested under quasi-static crush loads. The thermoplastic 3D-FRC at 45° trigger angle demonstrated 31 higher specific energy absorption (SEA), and 17 higher average crushing stress. This improved performance is attributed to higher fragmentation failure mechanisms, which absorbed more energy. These results elucidate that the resin-infused thermoplastic composites are suitable for higher energy absorption and lightweight design for automotive and sports applications. © 2021 Elsevier Ltd